THE IMPORTANCE OF TEACHING STERILIZATION IN MIDWIFERY EDUCATION (Modern education and development, 2025)
Sterilization is a fundamental concept in midwifery and nursing practice. It ensures the prevention of infections, safeguards maternal and neonatal health, and maintains the integrity of healthcare procedures. This article discusses the significance of sterilization in midwifery education, teaching methods, and its integration into nursing curricula.